Joining sheets to tubes by annular sheet squeezing. (August 2019) - Alves, L.M.; Silva, F.L.R.; Afonso, R.M.; Martins, P.A.F.
Abstract: This paper proposes a new joining by forming process to secure a sheet to a tube away from the tube end. The process is an alternative to welding, adhesive bonding, mechanical fastening or riveting and consists of squeezing the sheet adjacent to the outer tube radius, instead of applying direct loading on the tube itself as is customary in existing joining by forming processes. This process is cost effective, can be easily used on site and prevents cracking of the plastically deformed beads in tubular materials with low fracture toughness. The presentation combines experimentation and finite element modelling to identity the major process parameters, understand their influence in plastic flow and characterize the different modes of deformation that lead to acceptable and unacceptable joints. Utilization of a deformation-zone geometry parameter Δ, defined as the ratio of the sheet thickness to the cross-section recess length of the punch, is successfully utilized to characterize plastic flow inside the sheet thickness and to establish fundamental design rules. Appropriate values of the deformation-zone parameter in the range Δ = 2 − 3 and placed in-between the limiting values corresponding to inhomogeneous and homogeneous deformation, revealed adequate to obtain sound sheet-tube connections. The maximum pull-out forces are sensitive to the direction of applied loading due to the non-symmetric shape of the joints but no detachments were observed for forces up to 2 kN. Highlights: New joining by forming process to secure a sheet to a tube away from the tube end. Process squeezes the sheet adjacent to the tube, instead of applying loading on the tube itself. A deformation-zone parameter is used to characterize plastic flow and establish design guidelines. Validation by experimentation, numerical modelling and destructive pull-out testing.